Islamic Republic of Mauritania : Fifth Review Under the Extended Credit Facility Arrangement, and Request for Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Mauritania. (International Monetary Fund, 2021)
The COVID-19 pandemic continues to impose severe social and economic hardships in Mauritania, with a sharp contraction of output expected in 2020. The authorities have responded swiftly to the shock with measures to contain the pandemic and alleviate its fallout. They are prioritizing health spending and targeted support to the most vulnerable households and sectors in the economy. Nevertheless, conditions have weakened since the emergency disbursement under the Rapid Credit Facility in April 2020 (SDR 95.68 million, about USD 130 million or 74.3 percent of quota) and wider external and fiscal financing gaps are projected.